Proposed equations for predicting body composition of male wistar rats - Cossio-Bolaños, Marco Antonio (2010)
Introduction: Assessment of body composition is important as it allows splitting body weight in muscle weight, fat weight, bone weight and residual weight, both in humans and animals. Objectives: To validate somatic equations to predict a tri-compartment model of body composition (fat weight, fat free weight and residual weight) in male Wistar rats. Design: Descriptive transversal type study. Setting: Faculty of Biology, State University UNICAMP, Sao Paulo, Brazil. Biological material: Male Wistar rats. Methods: The study evaluated body weight (g) in 10 average age (X = 98.00 ± 10.40 days) male Wistar rats. They were sacrificed and splitting of fat weight (skin), fat free weight (muscle and bone) and residual weight (PR) (g) was done. Results were analyzed by arithmetic mean (X), standard deviation (SD) and Pearson product moment correlations (r) descriptive statistics. To predict components single and multiple regression statistics were applied, with weight body (g) and age (days) as independent variables. On the other hand, to verify agreement between in vitro method of dissection and regression equations Bland and Altman’s plotting were used. Main outcome measures: Somatic equations validation to predict rat’s corporal composition. Results: We observed high correlation coefficients (r) with body weight and age, which led to equations to allow prediction of the fat weight (PG=-31.6+(0.361*PT)-(0.345*age) (R2=0.73) and fat free weight (PLG=19.9+(0.453*PT)+(0.114*age) (R2=0.94). However, residual weight (PR) was obtained by mathematical deduction (PR = total weight -(PLG + PG)). Additionally, the Bland and Altman’s plotting allowed determining high concordance between the two procedures. Conclusion: Regression equations as doubly indirect method (three-compartment model) allow predicting 84 to 112 day-old male Wistar rats’ body composition.